PLANNING EARTHQUAKE RESISTANT UPPER BUILDING STRUCTURES WITH MOMENT GRABBING FRAME SYSTEM IN THE MARDHIKA PARK APARTMENT BUILDING 20 FLOORS TAMBUN – BEKASI - Holis Muhlisin; Ribut Nawang Sari; Sukatja Sukatja (Jakarta Global University, 2022)
Indonesia is an area with a high level of vulnerability to earthquake disasters, where this earthquake has caused a lot of losses and damage to building structures. Therefore, to reduce the risk due to the earthquake, it is necessary to plan earthquake-resistant building structures. The structural planning of building construction is needed to get the most effective and efficient dimensions and configuration of the structure. Collapsed buildings that are not strong enough to withstand lateral loads caused by the earthquake have resulted in significant loss of property and even lives. The purpose of writing this thesis is to design an earthquake-resistant Mardhika Park Apartment Building with a moment-resisting frame system (SRPM) which is planned in accordance with SNI 1726:2019 Earthquake (Earthquake Resistance Planning Procedures for Building and Non-Building Structures), SNI 2847 for Reinforced Concrete: 2019 (Requirements for structural concrete for buildings and their explanations), and the loading in accordance with SNI 1727:2020 for (Minimum Loads for Design of Buildings and Other Structures). The structural design of the Mardhika Park Apartment Building includes the design of this superstructure which includes columns, beams, and floor plates. Then the loads that are reviewed for structural element planning are dead, live, and earthquake loads. To assist in calculating the structure is also used Software